Politik des Evangeliums = Political of the Gospel Festschrift für Wolfgang Palaver - Guggenberger, Wilhelm; Regensburger, Dietmar; Wandinger, Nikolaus (innsbruck university press, 2023)
Can a convinced Catholic be an enthusiastic homo politicus, or does he perhaps even have to be? Those who know Wolfgang Palaver are aware that he is both and that he neither falls for the temptation of a theocratic integralism nor resigns himself to the relegation of religious convictions to the realm of the private. He leaves no doubt about the necessity of the separation of church and state and a distinction between religion and politics. For the believer, however, both are to be justified from within his religion. In the tension between the church's questionable claim to power and its necessary social commitment, which can probably never be completely resolved, Palaver sometimes speaks of the fact that it is more a matter of developing a theological politics than a political theology; of finding a way how we as believers can act politically in such a way that our world becomes more open to the coming of the Kingdom of God promised by Christ. This supposedly could be called a politics of the gospel. The contributions revolve around the question what the orientation to the kingdom of God can mean for shaping the world, how people can live their faith in a politically responsible way in a plural world, and in what way justice and peace are expressions of the kingdom of God and at the same time forms of life shaped in freedom by people. They thus take up a general bass that runs through the academic work and political commitment of Wolfgang Palaver and continue to play it in variations, as a many-voiced thanks to a colleague on the occasion of his farewell from his professional life.